2023
DOI: 10.3390/medicina59030525
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Diagnostic Ultrasound of the Vagus Nerve as a Surrogate Marker for Autonomic Neuropathy in Diabetic Patients

Abstract: Background and Objectives: Diagnostic ultrasound of the vagus nerve has been used to examine different polyneuropathies, and it has been suggested to be useful as a marker of autonomic dysfunction in diabetic patients. Materials and Methods: We analyzed the cross-sectional area (CSA) of the right vagus nerve of 111 patients with type 2 diabetes in comparison to 104 healthy adults and 41 patients with CIDP (chronic inflammatory demyelinating polyneuropathy). In the diabetes group, sympathetic skin response (SSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This indicates that more severe and/or chronic DPN results in higher NfL and more atrophic vagus nerves. However, another conducted study, showed that mean vagus nerve CSA did not differ in patients with and without DPN, and that a reliable diagnosis cannot be performed based on the vagus nerve measurement of a single person alone 44 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that more severe and/or chronic DPN results in higher NfL and more atrophic vagus nerves. However, another conducted study, showed that mean vagus nerve CSA did not differ in patients with and without DPN, and that a reliable diagnosis cannot be performed based on the vagus nerve measurement of a single person alone 44 …”
Section: Discussionmentioning
confidence: 96%
“…However, another conducted study, showed that mean vagus nerve CSA did not differ in patients with and without DPN, and that a reliable diagnosis cannot be performed based on the vagus nerve measurement of a single person alone. 44 Besides studying CSA in DPN, other parameters, such as changes in echogenicity and neural flow have been described, but less frequently. Our study showed predominance of the hypoechoic nerve pattern, with a loss of honeycomb appearance and presence of blurred boundaries along the course of different nerves (P < .05).…”
Section: Discussionmentioning
confidence: 99%